Information and knowledge organisation in digital humanities : global perspectives - Golub, Koraljka; Liu, Ying-Hsang (Digital Research in the Arts and Humanities, 2022)
Information and Knowledge Organisation explores the role of knowledge organisation in the digital humanities. By focusing on how information is described, represented and organised in both research and practice, this work furthers the transdisciplinary nature of digital humanities. Including contributions from Asia, Australia, Europe, North America and the Middle East, the volume explores the potential uses of, and challenges involved in, applying the organisation of information and knowledge in the various areas of Digital Humanities. With a particular focus on the digital worlds of cultural heritage collections, the book also includes chapters that focus on machine learning, knowledge graphs, text analysis, text annotations and network analysis. Other topics covered include: semantic technologies, conceptual schemas and data augmentation, digital scholarly editing, metadata creation, browsing, visualisation and relevance ranking. Most importantly, perhaps, the book provides a starting point for discussions about the impact of information and knowledge organisation and related tools on the methodologies used in the Digital Humanities field. Information and Knowledge Organisation is intended for use by researchers, students and professionals interested in the role information and knowledge organisation plays in the Digital Humanities. It will be essential reading for those working in library and information science, computer science and across the humanities. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.